A Nomogram for the Prediction of Cessation of Migraine Among Patients With Patent Foramen Ovale After Percutaneous Closure - Zhao, Enfa; Xie, Hang; Zhang, Yushun (Frontiers in Neurology, 2020)
Objective: This study aimed to develop and validate a nomogram to predict cessation of patent foramen ovale (PFO) related migraine patients after percutaneous closure. Methods: A total of 247 eligible patients with PFO and migraine after percutaneous closure between May, 2016 and May, 2018 were divided into a development cohort (n=149) and a validation cohort (n=98). The primary end point was cessation of migraine at follow-up of 1 year after the procedure measured by the Migraine Disability Assessment Score (MIDAS). In the development cohort, the LASSO regression was used data dimension reduction. A multivariable logistic regression analysis was used to develop the predicting nomogram. The performance of the nomogram was assessed by concordance index (C-index), calibration and clinical usefulness. The results were validated in the validation cohort. Results: Migraine with aura, history of antiplatelet, and the right-to-left shunt (RLS) at rest were identified as significant predictors based on the analysis of multivariate logistic regression. The nomogram incorporating these variables showed good calibration and discrimination in the development cohort with C-index of 0.906 (95%CI: 0.847-0.965), which was confirmed using the validation cohort with C-index of 0.827 (95%CI: 0.751-0.903). The nomogram showed good agreement between prediction by nomogram and actual observation. Furthermore, the decision curve indicated that the novel nomogram was clinically useful. Conclusion: The novel nomogram showed favorable predictive accuracy for cessation of migraine among patients with PFO after percutaneous closure and might provide constructive guidance in clinical decision making.